2018
DOI: 10.1016/j.clcc.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine Plus Oxaliplatin and Bevacizumab, Followed by Maintenance Treatment With Capecitabine and Bevacizumab for Patients Aged > 75 Years With Metastatic Colorectal Cancer

Abstract: CAPOX/Bev, followed by Cap/Bev as maintenance treatment, is safe and effective in terms of PFS and OS for elderly patients aged > 75 years with mCRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In contrast, few studies showed that treatment with chemotherapy was signi cantly effective in prolonging OS in super-elderly patients. In a previous study of chemotherapy under the age of 75, the most frequent adverse event ≥ grade 3 was neutropenia, with grade 3 neutropenia reported in 11.1% of patients; meanwhile, grade 3 fatigue was only reported in 2.8% of patients [8]. In our study, most patients in the super-elderly group (n = 10, 83%) received combination chemotherapy, the most common of which was an oxaliplatin-based regimen.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In contrast, few studies showed that treatment with chemotherapy was signi cantly effective in prolonging OS in super-elderly patients. In a previous study of chemotherapy under the age of 75, the most frequent adverse event ≥ grade 3 was neutropenia, with grade 3 neutropenia reported in 11.1% of patients; meanwhile, grade 3 fatigue was only reported in 2.8% of patients [8]. In our study, most patients in the super-elderly group (n = 10, 83%) received combination chemotherapy, the most common of which was an oxaliplatin-based regimen.…”
Section: Discussionsupporting
confidence: 48%
“…The study included 36 patients (13 patients aged ≥ 80 years), and 21 patients (58.3%) received second-line chemotherapy. The median PFS and OS was 8.8 months (95% CI: 6.7-10.3 months) and 20.8 months (95% CI: 16.1-26.4 months), respectively [8].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, drug combination therapies have become increasingly popular to reduce drug side effects and overcome chemoresistance 6. Combination of oxaliplatin with conventional chemotherapy drugs such as capecitabine has improved the survival of colon cancer patients 7. Alantolactone is a sesquiterpene lactone isolated from the roots of Inula helenium L , a traditional chinese herbal medicine which has been shown to possess strong anti-inflammatory and antitumor activities 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…It can also reduce the risk of recurrence in patients with high-risk colon cancer findings at surgery. 5-Fluorouracil (5-FU) and salinomycin (Sal) are common chemotherapeutic agents used to treat with CRC or recurrence after CRC surgery [47]. However, these drugs usually lead to severe side effects, including hand-foot syndrome, neuropathy, and allergic or sensitivity reactions [8,9].…”
Section: Introductionmentioning
confidence: 99%